A new role of anterograde motor Kif5b in facilitating large clathrin-coated vesicle mediated endocytosis via regulating clathrin uncoating. Issue 1 (December 2018) - Ni, Yan-Xiang; Zhou, Nan; Xue, Wen-Qian; Rong, Li; Yung, Wing-Ho; Lin, Rao-Zhou; Kao, Richard; Duan, Zhi-Gang; Sun, Hai-Tao; Gong, Hua-Rui; Tang, Xu-Ming; Liu, Meng-Fei; et al.
Abstract Kif5b-driven anterograde transport and clathrin-mediated endocytosis (CME) are responsible for opposite intracellular trafficking, contributing to plasma membrane homeostasis. However, whether and how the two trafficking processes coordinate remain unclear. Here, we show that Kif5b directly interacts with clathrin heavy chain (CHC) at a region close to that for uncoating catalyst (Hsc70) and preferentially localizes on relatively large clathrin-coated vesicles (CCVs). Uncoating in vitro is decreased for CCVs from the cortex ofkif5b conditional knockout (mutant) mouse and facilitated by adding Kif5b fragments containing CHC-binding site, while cell peripheral distribution of CHC or Hsc70 keeps unaffected by Kif5b depletion. Furthermore, cellular entry of vesicular stomatitis virus that internalizes into large CCV is inhibited by Kif5b depletion or introducing a dominant-negative Kif5b fragment. These findings showed a new role of Kif5b in regulating large CCV-mediated CME via affecting CCV uncoating, indicating Kif5b as a molecular knot connecting anterograde transport to CME.